Metabolic syndrome and its associations with socio-demographic and behavioral risk factors in the Russian population aged 25-64 years - Yu. A. Balanova; A. E. Imaeva; V. A. Kutsenko; A. V. Kapustina; G. A. Muromtseva; S. E. Evstifeeva; S. A. Maksimov; N. S. Karamnova; E. B. Yarovaya; S. A. Shalnova; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2020)
Aim. To assess the associations of metabolic syndrome (MS) with sociodemographic and  behavioral factors  in the  Russian population  aged 25-64 years.Material and methods. As part of the ESSE-RF 2 study, representative samples of the population of four Russian regions (Krasnodar Krai, Omsk and Ryazan Oblasts, Republic of Karelia) were examined: men (n=3011) and women (n=3721) aged 25-64 years. The response rate was approximately 80%. The study was approved by the Independent Ethics Committee of National Medical Research Center for Therapy and Preventive Medicine. All subjects were interviewed using a standard questionnaire. We analyzed the region and type of residence (urban/ rural area), age, educational level, marital and economic status, behavioral habits, and medical history data. Anthropometric measurements were performed. Blood pressure (BP) was measured with an Omron BP monitor. Lipid profile were assessed. MS was diagnosed according to the IDF criteria (2006). Statistical analysis was performed using the R 3.6.1 software package.Results. Abdominal obesity (AO) was found in 49,7% of men and 61,6% of women. Obesity according to body mass index was noted in 31,6% of subjects (men — 28,6% and women — 34%). MS prevalence in the entire sample was 33,0% and increased with age. In the group of subjects 35-44 years old, the prevalence of MS was significantly higher among men, and among those 55-64 years old — among women. We also found that AO in combination with two MS components was observed in 17,2% of participants; AO  with three components  — in 11,8%, AO with four components — in 4%. The highest prevalence of MS was noted in theRyazan region (men — 42,0%, women — 37,4%), the lowest — in theRepublic ofKarelia (men — 25,8%, women — 29,6%). In men, age-adjusted univariate logistic regression revealed significant associations of MS with former smoking, low physical activity, and alcohol abuse. Elevated BP and lipid profile abnormalities were significantly associated with low income level. AO was significantly associated with marriage. Similarly, the risk of diabetes and elevated blood glucose levels was lower in single men. Among women, the risk of MS was higher in those without higher education, with low income, smoking, and low consumption of vegetables and fruits. Women living in rural areas have a higher risk of AO and high BP. The risk of lipid metabolism disorders was higher among women with secondary education. Most of these associations were confirmed by multivariate analysis.Conclusion. MS was diagnosed in 33% of Russians aged 25-64 years. The proportion of people with MS increases with age, which, due to the  life expectancy increase, suggests an increase in the total number of MS people. Risk factors associated with MS in women are smoking, insufficient consumption of vegetables and fruits, no higher education, and low income. In men, MS are associated with excessive alcohol consumption, smoking, and low physical activity. MS prevalence can be reduced by changing the lifestyle and habits, and if necessary, in combination with drug therapy.